Prevalence of anxiety among pre-clinical medical students: A cross-sectional study - Banstola, Sanju; Lamichhane, Sabina (Journal of Gandaki Medical College-Nepal, 2024)
Introduction: A major worldwide health problem, anxiety disorders have detrimental morbidity and death rates. The study aimed to assess the status of generalized anxiety disorder and its association with related explanatory variables among medical college. Methods: A cross-sectional study was conducted among MBBS students of Gandaki Medical College studying in 1st and 2nd years using a self-administered questionnaire. The study was conducted from February 14 to 28, 2024. The study used a scale to measure anxiety levels using a 4-point Likert-scale Generalized Anxiety Disorder (GAD) with scores ranging from minimal 0 to maximum 21 Chi-square tests were applied at a 5% level of significance to find out the association of anxiety categories with respondents’ characteristics. Results: Out of 100 total respondents, 51% of the respondents were male, 41% were at age of 20 or below, and 94% were from the Hindu religion. Of total, over 25% of respondents reported daily nervousness, anxiety, and worry, while 31% experienced excessive worry and 25% experienced easily annoyed or irritable symptoms. The study found that 67% had generalized anxiety disorder including 27% had mild anxiety, 17% had moderate anxiety, and 23% had severe anxiety. Out of the total 21 scores, the GAD score in the study was found to have a mean score of 8.86. In addition, the study found a significant association of respondents’ sex and screen time with anxiety, but no significant association was found with age, academic year, caste, family type, or sleep hour. Conclusions: This study highlights a relatively higher level of generalized anxiety disorder among medical students, emphasizing the need for early detection, preventative measures, and treatment programs to improve their quality of life.